Implementasi Sistem Pendukung Keputusan Penentuan Siswa Terbaik Dengan Metode Complex Proportional Assessment (COPRAS) - Deri Setiawan (Journal of Decision Support System Research, 2024)
Due to the high level of competence between students and schools, SMA Muhammadiyah 2 Medan needs to select the best and outstanding students in order to compete among students by involving various considerations. The consideration of the criteria taken are the average value of the report card, attitude value, skill value, extracurricular, and number of attendance. Currently, SMA Muhammadiyah 2 Medan is still conducting an assessment process that involves the subjectivity of the teaching teacher or homeroom teacher, resulting in a less than optimal assessment, due to partiality. Therefore, the researchers built a Decision Support System (SPK) application for selecting the best students using the Complex Proportional Assessment (COPRAS) method. The COPRAS method testing uses 10 alternatives and 5 existing criteria. The results showed that the Decision Support System (SPK) could help the SMA Muhammadiyah 2 Medan to complete the selection of the best students correctly and accurately.